Cytomegalovirus antibody level and progression of chronic heart failure - S. N. Shilov; E. N. Berezikova; S. D. Mayanskaya; I. V. Pankova; B. B. Pinkhasov; A. A. Popova; D. Zh. Tabdaeva; A. D. Vikhreva (Сибирский научный медицинский журнал, 2024)
This study demonstrates the relationship between IgG titer to cytomegalovirus (CMV) and the proinflammatory cytokine TNF-α and IL-1β concentration, the prognosis after hospitalization of patients due to decompensation of chronic heart failure (CHF) during 24 months of observation. Material and methods. We examined 132 patients with CHF of ischemic etiology (age 59.0 [54.0; 63.5] year, median [lower quartile; upper quartile]), hospitalized for CHF decompensation. Patients were included in the study after stabilization of CHF decompensation before discharge from the hospital. Subsequently, patients were prospectively monitored for 24 months. Upon inclusion in the study, TNF-α, IL-1β plasma concentration was determined, before discharge from the hospital and after 24 months – the titer of IgG antibodies to CMV. Results. The titer of IgG to CMV in the cohort of patients was 1356 [835; 1931] units/ml. Patients were divided into tertiles 1, 2 and 3 with an antibody titer of less than 923, from 923 to 1811 and more than 1811 units/ml, respectively (44 persons in each group). Individuals from the tertile 3 group were more likely to have IV functional class CHF (p = 0.025), and also had a higher content of pro-inflammatory cytokines (p = 0.001 for TNF-α and p = 0.019 for IL-1β), and the number of hospitalizations due to decompensation of CHF, worsening functional class of CHF and deaths during 24 months of observation than in patients of tertile 1. Conclusions. With an increased level of IgG to CMV in patients with CHF, there is an increase in the concentration of pro-inflammatory cytokines and the risk of adverse cardiovascular events within 24 months after an episode of CHF decompensation compared to patients with lower antibody levels. The activity of the inflammatory process, which is influenced by CMV infection, on the background of immunosuppression in patients with CHF, is likely an important trigger for the progression of cardiovascular pathology and mortality.